A BIOPSYCHOSOCIAL MODEL OF SOCIAL ANXIETY AND SUBSTANCE USE. Issue 3 (13th December 2012) - Buckner, Julia D.; Heimberg, Richard G.; Ecker, Anthony H.; Vinci, Christine
<x xml:space="preserve">Abstract</x> Emerging prospective work suggests that individuals with social anxiety disorder (SAD) may be at particular risk for developing substance use disorders (SUD). Yet, little is known about why this may be so. Most research has utilized existing theories of substance use (e.g. tension reduction‐based theories) to understand SAD–SUD relations. However, these theories do not address why individuals with social anxiety, in particular, experience such high rates of substance‐related problems. A possible explanation may lie in the nature of social anxiety itself, which is characterized not only by chronically elevated negative affective states, but by low positive affect, fear of scrutiny, and social avoidance. These aspects of social anxiety may work in concert to place these especially vulnerable individuals at risk for SUD. The current paper presents a biopsychosocial model of SAD‐SUD comorbidity that focuses on several specific facets of social anxiety that may be especially related to SUD risk. The utility of this model is evaluated via a review of the literature on the relations between SAD and substance‐related behaviors.